The information needs of people with COPD-The holistic approach with special reference to gender and time since diagnosis - Hannele Siltanen; Tiina Aine; Heini Huhtala; Marja Kaunonen; Eija Paavilainen (Wiley, 2021)
Abstract Aims The aim of this study was to determine what kinds of unmet information needs people with COPD have and whether there are differences in information needs between genders or based on the time since COPD diagnosis. Design A descriptive cross‐sectional study. Methods Data on people with COPD (N = 169) were collected from a two‐part questionnaire distributed via website. On the first part, information needs concerning the medical aspects of self‐management were measured by the Lung Information Needs Questionnaire (LINQ). On the second part, which was developed specifically for this study, a more holistic view of self‐management counselling was sought. Statistical methods were used to analyse the data. Results The respondents had wide‐ranging information needs in many areas of COPD self‐management. The most often reported areas of unmet information needs included exacerbations, diet, fatigue, stress and anxiety, palliative care and sexual life. The information needs varied by gender and time since COPD diagnosis.